High anti-Mullerian hormone level is adversely associated with cumulative live birth rates of two embryo transfers after the first initiated cycle in patients with polycystic ovary syndrome - Su, Nianjun; Zhan, Juanxiao; Xie, Meiling; Zhao, Ying; Huang, Cuiyu; Wang, Songlu; Liao, Liujun; Zhang, Xiqian; Liu, Fenghua (Frontiers in Endocrinology, 2023)
Objective: Anti-Mullerian hormone (AMH) has been recently identified as a potential predictor of livebirth rates (LBRs) following assisted reproductive technology (ART) treatment. This study aimed to investigate the association between AMH levels and the outcomes of in vitro fertilization (IVF) in patients with polycystic ovary syndrome (PCOS). Methods: Patients with PCOS initiating their first ovarian stimulation under the gonadotropin-releasing hormone antagonist protocol at the Guangdong Women and Children Hospital, China, were enrolled from November 2014 to September 2018. A total of 157 patients who underwent fresh embryo transfer (ET) cycles were included in group A, whereas 187 patients who underwent frozen–thawed ET cycles were included in group B. After the failure of the first ET cycle, 94 patients underwent the second ET cycle with frozen–thawed embryos. Of these 94 patients, 52 had failed the first fresh ET cycle (group C) and 42 had failed the first frozen–thawed ET cycle (group D). Successful embryo transfer was defined as livebirth. This retrospective cohort study addressed the association between AMH levels and pregnancy outcomes using logistic regression approaches. After adjusting for age, body mass index, antral follicle counts, baseline follicle-stimulating hormone levels and baseline progesterone levels, LBRs were compared among the four groups and the cumulative livebirth rate after two embryo transfers (TCLBR) was calculated. Results: The LBRs showed no differences among the four groups. Higher serum AMH levels were found to be associated with a lower TCLBR [adjusted OR 0.937 (0.888–0.987), P = 0.015]. In patients who underwent the second ET cycle, LBRs were inversely proportional to AMH levels [crude OR 0.904 (0.828–0.986), P = 0.022 versus adjusted OR 0.845 (0.754–0.946), P = 0.004, respectively]. In addition, the LBR was approximately 61%–78% lower in the group with AMH levels of >12 ng/mL [crude OR 0.391 (0.168–0.912), P = 0.030 versus adjusted OR 0.217 (0.074–0.635), P = 0.005, respectively]. Conclusions: Among PCOS patients high AMH level (>12 ng/ml) is found to be associated with low TCLBR and low LBR of the second embryo transfer cycles. The results provide limited clinical inferences and warrant further investigation.